A C, S bonded quasi-two-coordinate chromium(ii) complex showing field-induced slow magnetic relaxation behaviour. Issue 24 (7th June 2022) - Luo, Qian-Cheng; Ge, Ning; Zhai, Yuan-Qi; Wang, Teng-Bo; Sun, Lin; Sun, Qi; Li, Fanni; Ouyang, Zhongwen; Wang, Zhen-Xing; Zheng, Yan-Zhen
Abstract : The title compound was studied, which showed relatively large rhombic anisotropy and field-induced slow magnetic relaxation behaviour. Abstract : A C, S bonded quasi-two-coordinate Cr(ii ) complex, Cr(SAr*)2 (HSAr* = HSC6 H3 -2, 6(C6 H2 -2, 4, 6-Pr i 3 )2 ), has been synthesized according to literature precedent. Magnetic measurements, high-frequency/field electron paramagnetic resonance (HF-EPR) experiments and ab initio calculation studies show that the field-induced slow magnetic relaxation behaviour is caused by relatively weak axial magnetic anisotropy.